Posibles talentos deportivos para las pruebas de velocidad-atletismo en niños. - Caguas Chafla, Darwin Israel (2023)
Selection is nothing more than identifying talented individuals with a positive attitude toward the sport. The present study was conducted in the Gonzol educational unit, from Gonzol parish of Chunchi canton, Chimborazo province. The selection of possible sports talents in the speed- athletics test was carried out. The population in this descriptive study with a quantitative-qualitative approach with a non-experimental design was 72 students, with the participation of the entire population, 41 are male, and 31 are female. The software SPSS and Office Excel were used for the statistical analysis of the data. After analyzing the results obtained, it is only obtained that eight students have the conditions to practice speed athletics. From the analysis and interpretation of the results, conclusions and recommendations were stated that helped to offer a proposal for the future to be able to select sports talents in speed-athletics in the Gonzol parish.